Composite current collector and preparation method thereof, positive pole piece and secondary battery
By making grooves on the current collector to fill catalytic materials and lithium-rich materials to form composite fluid collections, the problems of catalytic material exposure and volume occupation are solved, and efficient lithium supplementation and energy density improvement are achieved.
Patent Information
- Application Number
- CN202411758421.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-02-25
AI Technical Summary
In the prior art, the combination of lithium-rich materials and catalytic materials has the problem of exposure of catalytic materials to the electrolyte, and the lithium-rich materials and catalytic materials extrude the volume space of the positive electrode active material, resulting in a decrease in the energy density of the battery and a shortened cycle life.
By making grooves on the current collector, filling the catalytic material and lithium-rich material to form a composite liquid collector, ensuring that the catalytic material is in close contact with the lithium-rich material, and the catalytic material is contained in the grooves to prevent it from being exposed to the electrolyte.
While achieving lithium supplementation effect, the first effect and energy density of the battery cell are improved, premature damage to catalytic materials and battery volume occupation problems are avoided, and the overall performance of the secondary battery is improved.
Smart Images

Figure CN119517993A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a composite current collector and a preparation method thereof, a positive electrode sheet and a secondary battery. Background Art
[0002] During the first cycle of charging of a lithium-ion battery, the solid electrolyte interface formed on the surface of the negative electrode will irreversibly consume the active lithium in the battery system, resulting in a decrease in the battery energy density and a shortened cycle life. Pre-lithiation technology is considered to be an effective way to solve the problem of active lithium loss in batteries. In the prior art, lithium-rich materials are added to the positive electrode slurry as lithium supplements, so as to use such compounds to supplement the positive electrode active material with lithium. However, due to the high decomposition voltage of lithium-rich materials, after the lithium-rich materials are mixed and coated as additives to the positive electrode slurry, the decomposition voltage of the lithium-rich materials will mostly not match the positive electrode active material.
[0003] In the prior art, in order to solve the problem of high decomposition voltage of lithium-rich materials, a catalytic material and a lithium-rich material are mixed, and the catalytic material is used to catalyze and reduce the decomposition voltage of the lithium-rich material. However, the common combination method of lithium-rich materials and catalytic materials in the prior art is to grow the catalytic material outside the lithium-rich material (or grow the lithium-rich material outside the catalytic material). The disadvantage of this combination method is that after the lithium-rich material is delithiated, the bonding strength between the catalytic material and the lithium-rich material is weakened, and the catalytic material lacks attachment sites, resulting in the catalytic material being exposed to the electrolyte for a long time to catalyze the electrolyte; and, both the lithium-rich material and the catalytic material will occupy the volume space of the positive electrode active material. Therefore, how to solve the problem of the catalytic material being exposed to the electrolyte after the lithium-rich material is delithiated, and the lithium-rich material and the catalytic material occupying the volume space of the positive electrode active material has become a key issue. Summary of the invention
[0004] The purpose of the present application is to provide a composite current collector and a preparation method thereof, a positive electrode plate and a secondary battery, so as to solve the problem that the catalytic material is exposed to the electrolyte and the lithium-rich material and the catalytic material occupy the volume space of the positive electrode active material.
[0005] To achieve the purpose of this application, this application provides the following technical solutions:
[0006] In a first aspect, the present application provides a composite current collector, comprising a current collector having grooves, at least part of the grooves being filled with a catalytic material, and the composite current collector further comprising a lithium-rich material in contact with the catalytic material.
[0007] In one embodiment, the lithium-rich material is filled in the groove, and the filling height of the lithium-rich material and the catalytic material in the groove is not lower than the opening surface of the groove on the current collector.
[0008] In one embodiment, along the thickness direction of the current collector, the thickness of the catalytic material in the groove is 2 μm to 10 μm.
[0009] In one embodiment, along the thickness direction of the current collector, the thickness of the lithium-rich material is 100 nm to 500 nm.
[0010] In one embodiment, the lithium-rich material includes a plurality of particles, and the particle size of the particles is 20 nm to 300 nm.
[0011] In one embodiment, the mass ratio of the lithium-rich material to the catalytic material is 1:(10-20).
[0012] In one embodiment, the catalytic material includes a metal element and / or an alloy, and the catalytic material is sputtered on the surface of the groove.
[0013] In one embodiment, the porosity of the current collector is 60% to 80%.
[0014] In one embodiment, the depth of the groove is 1 / 2 to 4 / 5 of the thickness of the current collector.
[0015] In one embodiment, the opening diameter of the groove is 400nm to 800nm.
[0016] In one embodiment, along the thickness direction of the current collector, the groove extends in a constricted shape.
[0017] In one embodiment, at least a portion of the openings of the grooves are formed in one or more of a circular, ellipsoidal, and polygonal shape.
[0018] In a second aspect, the present application provides a method for preparing a composite current collector, comprising: making a groove on the current collector; respectively depositing a catalytic material and a lithium-rich material on the current collector, the catalytic material filling the groove, the lithium-rich material and the catalytic material being in contact, thereby obtaining the composite current collector.
[0019] In a third aspect, the present application provides a positive electrode plate, comprising a positive electrode material layer and a composite current collector as described in the first aspect, wherein the positive electrode material layer is coated on a surface of the composite current collector on a side where a groove is provided.
[0020] In one embodiment, the composite current collector further includes a porous carbon layer, which covers the surface of the current collector and the lithium-rich material; and the positive electrode material layer is coated on the surface of the porous carbon layer away from the groove.
[0021] In one embodiment, the compaction density of the porous carbon layer is 1.0 g / cm 3~2.0g / cm 3 .
[0022] In a fourth aspect, the present application provides a secondary battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises the positive electrode plate as described in the third aspect.
[0023] The present application accommodates lithium-rich materials and catalytic materials in a current collector through grooves, thereby obtaining an integrated composite current collector with a lithium replenishing effect, and the composite current collector has the following effects: 1) The composite current collector can ensure the lithium replenishing effect while effectively improving the initial efficiency and energy density of the battery cell; 2) The lithium-rich material and the catalytic material are parts of the composite current collector, and the two are in close contact, thereby improving the catalytic effect of the catalytic material on the lithium-rich material; 3) After the catalytic material catalyzes the lithium-rich material, the catalytic material is accommodated in the groove, thereby avoiding its long-term exposure to the electrolyte to catalyze the electrolyte; 4) Neither the lithium-rich material nor the catalytic material is in the positive electrode material layer, and the two will not occupy the volume space of the positive electrode active material, thereby improving the energy density of the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0025] Figure 1 is a schematic cross-sectional view of a composite current collector according to an embodiment;
[0026] Figure 2 is a schematic top view of a composite current collector according to an embodiment;
[0027] Figure 3 is a flow chart of a method for preparing a composite current collector according to an embodiment;
[0028] Figure 4 is a flow chart of step S20 of one embodiment;
[0029] Figure 5 is a scanning electron microscope image (SEM) of a commercial aluminum foil provided in Example 1;
[0030] Figure 6 is a scanning electron microscope image (SEM) of the porous aluminum foil after electrochemical etching in Example 1;
[0031] Figure 7 is a scanning electron microscope image (SEM) of the composite current collector prepared in Example 1;
[0032] Figure 8 This is a scanning electron microscope (SEM) image of the composite current collector prepared in Example 1 from another viewing angle. DETAILED DESCRIPTION
[0033] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0034] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used in this application and in the specification are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used in this application includes any and all combinations of one or more of the related listed items.
[0035] It should be noted that the "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of a particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0036] All steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, a method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, a method may also include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b, etc.
[0037] In conjunction with the accompanying drawings, some embodiments of the present application are described in detail below. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.
[0038] The present application provides a composite current collector, please refer to Figure and Figure 2 .
[0039] In one implementation, please refer to Figure 1 The composite current collector includes a current collector 10 having a groove 11, at least part of the groove 11 is filled with a catalytic material 30, and the composite current collector also includes a lithium-rich material 20 in contact with the catalytic material 30. Specifically, the composite current collector provided in the present application can be used in the positive electrode. The composite current collector is a key component in a lithium-ion battery, and its main functions include connecting active substances, collecting current, and carrying electrode materials.
[0040] In the present application, the lithium-rich material 20 and the catalytic material 30 are accommodated in the current collector 10 through the groove 11, and an integrated composite current collector with a lithium replenishing effect is obtained. The composite current collector has the following effects: 1) The composite current collector can ensure the lithium replenishing effect while effectively improving the first efficiency and energy density of the battery cell; 2) The lithium-rich material 20 and the catalytic material 30 are parts of the composite current collector, and the two are in close contact, thereby improving the catalytic effect of the catalytic material 30 on the lithium-rich material 20; 3) After the catalytic material 30 catalyzes the lithium-rich material 20, the catalytic material 30 is accommodated in the groove 11, thereby avoiding its long-term exposure to the electrolyte to catalyze the electrolyte; 4) Neither the lithium-rich material 20 nor the catalytic material 30 is in the positive electrode material layer, and the two will not occupy the volume space of the positive electrode active material, thereby improving the energy density of the secondary battery.
[0041] In one embodiment, the current collector 10 may be a metal foil or a composite foil. As an example of a metal foil, an aluminum foil may be used. The composite foil may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include at least one of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).
[0042] In one embodiment, the current collector 10 includes two surfaces facing each other in the thickness direction X, either or both of which can be used as a coating surface, and the coating surface is used to set the positive electrode material layer. In the following text, one surface on the current collector 10 is used as the coating surface for description, and the thickness direction X in the following text refers to the thickness direction X of the current collector 10. Of course, when the positive electrode material layer needs to be set on both sides of the current collector 10, both sides of the current collector 10 can be set in the manner provided in the following embodiments.
[0043] In one embodiment, the current collector 10 is provided with a groove 11, and the groove 11 extends toward the inside of the current collector 10 along the thickness direction X of the current collector 10. The extension path of the groove 11 obtained by cross-sectioning the current collector 10 along the thickness direction X of the current collector 10 is not specifically limited, and can be a straight line extension or a curve extension. The groove 11 is used to accommodate the catalytic material 30.
[0044] In one embodiment, the chemical formula of the lithium-rich material 20 includes Li x1 C y1 O z1 , where 0<x1≤2,y1> 0, z1>0. In a specific embodiment, the lithium-rich material 20 may include Li 2 C 2 O 4 (lithium oxalate), Li 2 CO 3 (lithium carbonate), Li 2 C 3 O 3 (Lithium trioxide), Li 2 C 4 O 4 (lithium butynedioate), Li 2 C 6 O 6 , Li 2 C 3 O 5 (lithium acetonate), and Li 2 C 4 O6 It can be understood that the lithium-rich materials 20 are all materials with high decomposition voltages, so after the above materials are mixed with the catalytic material 30, their decomposition voltages can be reduced.
[0045] In one embodiment, the lithium-rich material 20 may also include LiOH (delithiation potential 4.8V), Li 4 SiO 4 (lithiation potential 4.5V), Li 3 PO 4 (The delithiation potential exceeds 4V). The delithiation of these materials requires a relatively high charging voltage, which will cause the lithium-ion battery to produce oxygen during the first charge and discharge. The generated oxygen is further oxidized to cause the electrolyte to oxidize and decompose, thereby reducing the safety and performance of the lithium-ion battery. Therefore, the solution provided in this application can be applied to such materials.
[0046] In one embodiment, the lithium-rich material 20 mentioned above may be undoped or modified by doping, or may be surface coated, pre-lithiation treated, etc. These lithium-rich materials 20 have high theoretical capacity and structural stability, can provide ample lithium ions, effectively replenish the irreversible lithium ions consumed by the formation of SEI film at the negative electrode, and improve the initial efficiency and overall electrochemical performance of the battery. It should be noted that the above lithium-rich materials 20 have long been industrially produced and do not need to be independently synthesized, so the raw material cost is low and the purity is high; and the selected lithium-rich materials 20 have high theoretical capacity, and the synthesized composite lithium-supplementing material has a high specific charging capacity and an excellent lithium-supplementing effect.
[0047] In one embodiment, the catalytic material 30 may include a metal element, specifically including but not limited to one or more of Co, Ni, Fe, Mn, Cr, V, Mo, Ti, Nb, Zr, Cu, and Mg.
[0048] In one embodiment, the catalytic material 30 may also include a metal compound, specifically including but not limited to one or more of metal oxides, metal nitrides, metal carbides, metal sulfides, and metal phosphides. The above metal compounds all have catalytic functions and can catalyze the decomposition of the lithium-rich material 20 at a lower potential, thereby increasing the lithium replenishment capacity.
[0049] In one embodiment, the catalytic material 30 may also include an alloy, wherein the alloy is composed of aluminum and other metals, and a heterojunction is formed between the metals in the alloy. It should be explained that the catalytic material 30 may be an alloy composed of a metal element and the metal in the current collector 10. Since the current collector 10 is an aluminum foil, the alloy may be an aluminum alloy. Specifically including but not limited to cobalt-aluminum alloy, nickel-aluminum alloy, iron-aluminum alloy, etc. It can be understood that the catalytic material 30 is an alloy, which actually introduces other metal heterogeneities into the current collector 10. The introduction of heterogeneity has a certain catalytic ability under the premise of not affecting the conductivity of the current collector 10 itself. The metal element can catalyze the decomposition of the lithium-rich material adsorbed on its surface, providing a lithium supplement effect.
[0050] In other embodiments, the catalytic material 30 may also include other types of materials such as carbon materials, ion conductor materials, semiconductor materials, etc. The type of the specific catalytic material 30 is not limited, but the catalytic material 30 may have one or more functions such as conductivity and catalysis.
[0051] In one embodiment, the lithium-rich material 20 is filled in the groove 11, and the filling height of the lithium-rich material 20 and the catalytic material 30 in the groove 11 is not lower than the opening surface of the groove 11 on the current collector 10. Specifically, the lithium-rich material 20 and the catalytic material 30 are both filled in the groove 11, and the thickness of the material in the groove 11 (including the lithium-rich material 20 and the catalytic material 30) is greater than or equal to the depth of the groove 11. Preferably, the lithium-rich material 20 and the catalytic material 30 fill the groove 11, so that the thickness of the material in the groove 11 is equal to the depth of the groove 11.
[0052] The present application fills both the lithium-rich material 20 and the catalytic material 30 in the groove 11, so that the lithium-rich material 20 can be evenly dispersed on the current collector 10 through the groove 11, which can avoid the problem of uneven distribution of the lithium-rich material 20 caused by coating, thereby improving the stability of the battery cell; the catalytic material 30 in the composite current collector can catalyze the decomposition of the lithium-rich material 20 at a lower voltage, so that the lithium-rich material 20 can fully release its capacity; at the same time, the groove 11 can accommodate the gas generated when the lithium-rich material 20 decomposes, thereby reducing the gas production of the battery.
[0053] In one embodiment, the form in which the lithium-rich material 20 and the catalytic material 30 are contained in the groove 11 is not limited. Either the lithium-rich material 20 or the catalytic material 30 can be in a granular form or in a dense layered form. In a specific embodiment, the lithium-rich material 20 can be in a granular form, and the catalytic material 30 can be in a dense layered form. Of course, the lithium-rich material 20 and the catalytic material 30 can also be both in a granular form.
[0054] In one embodiment, the lithium-rich material 20 and the catalytic material 30 may be arranged in layers in the groove 11, that is, along the thickness direction X, the lithium-rich material 20 and the catalytic material 30 independently form two layers in the groove 11, one of which is composed of the lithium-rich material 20, and the other is composed of the catalytic material 30, and the two layers may be directly connected or indirectly connected. Of course, in the thickness direction X, any one of the lithium-rich material 20 and the catalytic material 30 may be located above or below.
[0055] In one embodiment, the lithium-rich material 20 and the catalytic material 30 can also be mixed in the groove 11, that is, the lithium-rich material 20 and the catalytic material 30 are uniformly mixed together in the groove 11. Of course, the lithium-rich material 20 and the catalytic material 30 can also form a composite material, which is then accommodated in the groove 11, and the lithium-rich material 20 and the catalytic material 30 can form a composite material with a core-shell structure, such as the catalytic material 30 coated on the outer surface of the lithium-rich material 20. The catalytic material 30 of this structure can protect the lithium-rich material 20, reduce the erosion of the lithium-rich material 20 by external water vapor, and reduce gas production.
[0056] In one embodiment, the catalytic material 30 or the lithium-rich material 20 may be attached to the inner wall (including the bottom wall and the side wall) of the groove 11, and then the lithium-rich material 20 or the catalytic material 30 is contained in the groove 11. That is, the lithium-rich material 20 is indirectly connected to the inner wall of the groove 11 through the catalytic material 30.
[0057] In one embodiment, along the thickness direction X of the current collector 10, the catalytic material 30 is disposed at the bottom of the groove 11, and the lithium-rich material 20 is disposed on the catalytic material 30 and close to the opening of the groove 11. Specifically, the catalytic material 30 and the lithium-rich material 20 are layered, the catalytic material 30 is disposed at the bottom of the groove 11 (which may be connected to the bottom wall of the groove 11), and the catalytic material 30 may be the alloy in the above embodiment; the lithium-rich material 20 is disposed on the catalytic material 30, and the lithium-rich material 20 may be agglomerated with multiple particles.
[0058] In one implementation, please refer to Figure 1 The catalytic material 30 is arranged at the bottom of the groove 11, and a pore structure is formed in the catalytic material 30, so that the layer formed by the catalytic material 30 can also be used to absorb the gas generated by the lithium-rich material 20, that is, the gas is confined in the pore structure of the catalytic material 30, thereby reducing the gas production of the battery.
[0059] In one embodiment, along the thickness direction X of the current collector 10, the thickness of the catalytic material 30 is 2μm to 10μm. Specifically, satisfying the thickness of the catalytic material 30 within the above range can ensure that the catalytic material 30 exerts its effect and ensure the lithium replenishment capacity of the composite current collector. When the thickness of the catalytic material 30 is too small, the catalytic material 30 is too little to exert its effect; when the thickness of the catalytic material 30 is too large, the catalytic material 30 is too much, resulting in a reduction in the proportion of the lithium-rich material 20. Optionally, the thickness of the catalytic material 30 can be 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm.
[0060] In one embodiment, the thickness of the lithium-rich material 20 is 100 nm to 500 nm along the thickness direction X of the current collector 10. Specifically, if the thickness of the lithium-rich material 20 is within the above range, the capacity of the lithium-rich material 20 can be ensured. When the thickness of the lithium-rich material 20 is too small, the lithium-rich material 20 is too small, resulting in a decrease in the lithium replenishment capacity.
[0061] In one embodiment, the lithium-rich material 20 includes a plurality of particles, and the particle size of the particles is 20nm to 300nm. Specifically, satisfying the particle size within the above range can reduce the difficulty of preparing the particles and increase the density of the lithium-rich material 20 in the groove 11. When the particle size of the particles is too small, the difficulty of preparing the material increases; when the particle size of the particles is too large, the pores between the particles increase, resulting in a decrease in the density of the lithium-rich material 20 accommodated in the groove 11. Optionally, the particle size of the particles can be 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 100nm, 250nm, 300nm; at the same time, what is referred to here can be the particle size of the primary particles or the particle size of the secondary particles.
[0062] In one embodiment, the mass ratio of the lithium-rich material 20 to the catalytic material 30 is 1:(10-20). Specifically, satisfying the mass ratio of the lithium-rich material 20 to the catalytic material 30 within the above range can ensure that the catalytic material 30 can exert its effect and ensure the lithium replenishment capacity of the composite current collector. When the proportion of the catalytic material 30 is too small, the catalytic material 30 is too little to exert its effect; when the proportion of the catalytic material 30 is too large, the catalytic material 30 is too much, resulting in a reduction in the proportion of the lithium-rich material 20.
[0063] In one embodiment, the catalytic material 30 includes a metal element and / or an alloy, and the catalytic material 30 is sputtered on the surface of the groove 11. The catalytic material 30 can be attached to the inner wall surface of the groove 11 to form a catalytic material layer, so that the lithium-rich material 20 in the groove 11 is accommodated and arranged on the catalytic material layer.
[0064] In one embodiment, the porosity of the current collector 10 is 60% to 80%. Specifically, the porosity of the current collector 10 refers to the proportion of the groove 11 on the current collector 10 in the volume of the entire current collector 10. When the porosity of the current collector 10 is within the above range, the lithium replenishment capacity provided by the current collector 10 can be ensured, and the structural stability of the current collector 10 can be ensured. When the porosity of the current collector 10 is too small, the lithium replenishment capacity of the composite current collector decreases; when the porosity of the current collector 10 is too large, the structural stability of the current collector 10 deteriorates. Optionally, the porosity of the current collector 10 can be 60%, 62%, 64%, 66%, 68%, 70%, 72%, 74%, 76%, 78%, 80%.
[0065] In one embodiment, the depth of the groove 11 is 1 / 2 to 4 / 5 of the thickness of the current collector 10. Specifically, satisfying the depth of the groove 11 within the above range can ensure the lithium replenishment capacity provided by the current collector 10 and ensure the structural stability of the current collector 10. When the depth of the groove 11 is too small, the lithium replenishment capacity of the composite current collector decreases; when the depth of the groove 11 is too large, the structural stability of the current collector 10 deteriorates. Optionally, the depth of the groove 11 is 1 / 2, 3 / 5, 2 / 3, 7 / 10, or 4 / 5 of the thickness of the current collector 10.
[0066] In one embodiment, the opening diameter of the groove 11 is 400nm to 800nm. Specifically, satisfying the opening diameter of the groove 11 within the above range can ensure that the lithium-rich material 20 and the catalytic material 30 can be accommodated in the groove 11, and ensure that the size of the current collector 10 is not affected. When the opening diameter of the groove 11 is too small, it is difficult for the lithium-rich material 20 and the catalytic material 30 to be accommodated in the groove 11 through the opening; when the opening diameter of the groove 11 is too large, the current collector 10 will be thinned, affecting the specifications of the current collector 10. Optionally, the opening diameter of the groove 11 can be 400nm, 450nm, 500nm, 550nm, 600nm, 650nm, 700nm, 750nm, 800nm.
[0067] In one embodiment, along the thickness direction X of the current collector 10, the groove 11 extends in a constricted shape from the coating surface to the inside of the current collector 10. Specifically, the current collector 10 is cross-sectioned along the thickness direction X of the current collector 10, and the resulting groove 11 is in a constricted shape, wherein the opening diameter of the groove 11 on the coating surface is the largest. Optionally, the current collector 10 is cross-sectioned along the thickness direction X of the current collector 10, and the resulting groove 11 is in a triangular pyramid shape (inverted V shape) or an inverted trapezoid shape. In this way, the stability of the internal structure of the current collector 10 can be ensured, and the bottom diameter of the groove 11 is smaller, so that the wall thickness of the surrounding current collector 10 is larger, and it can be lower than the volume expansion of the current collector 10.
[0068] In one implementation, please refer to Figure 1 Along the thickness direction X of the current collector 10, the diameter of the groove 11 gradually decreases. It can be a uniform linear decrease, or the diameter of a certain section of the groove 11 remains unchanged, and the diameter of another section of the groove 11 decreases. Preferably, it is a uniform linear decrease.
[0069] In one implementation, please refer to Figure 2 In B, at least part of the grooves 11 extend in a linear shape. Specifically, the number of grooves 11 is multiple, and when observing the coating surface from a top view, it can be seen on the coating surface that the grooves 11 extend in a linear shape. Optionally, the grooves 11 may extend in a straight line or a curve. In a specific embodiment, the multiple grooves 11 are independent of each other, and the multiple grooves 11 extend in the same direction, and there is a spacing distance between two grooves 11. In other embodiments, the multiple grooves 11 are interconnected, that is, the multiple grooves 11 cross to form a network.
[0070] In one implementation, please refer to Figure 2 In A, at least part of the openings of the grooves 11 are formed into one or more of a circular, ellipsoidal, and polygonal shape. Specifically, there are multiple grooves 11, and when the coating surface is observed from a top view, it can be seen on the coating surface that the grooves 11 are in one or more of a circular, ellipsoidal, and polygonal shape. In a specific embodiment, the multiple grooves 11 are independent of each other, and the multiple grooves 11 are randomly distributed in a star-shaped pattern on the coating surface.
[0071] In one implementation, please refer to Figure 1 The composite current collector also includes a porous carbon layer 40, which covers the surface of the current collector 10 and the lithium-rich material 20. The porous carbon layer 40 includes a connected joint 41 and a recessed portion 42. The orthographic projection of the recessed portion 42 on the coating surface at least partially overlaps with the groove 11. In the thickness direction X, the thickness of the joint 41 is greater than or equal to the thickness of the recessed portion 42.
[0072] Specifically, a porous carbon layer 40 is disposed on the coating surface, and the porous carbon layer 40 closes the opening of the groove 11. It can be understood that, since the groove 11 is a concave portion on the coating surface, when the porous carbon layer 40 covers the coating surface, the portion of the porous carbon layer 40 located on the groove 11 will be concave downward to form a concave portion 42 lower than the surrounding area; and the porous carbon layer 40 disposed on the coating surface (the portion not on the groove) has a normal thickness, that is, the joint portion 41.
[0073] The present application further arranges a porous carbon layer 40 on the coating surface. The porous carbon layer 40 cooperates with the groove 11 to absorb the oxygen generated when the lithium-rich material 20 is decomposed, thereby improving the reliability of the battery cell; moreover, most of the gas generated by the lithium-rich material 20 enters the porous carbon layer 40 instead of being retained in the groove 11, which can avoid the deformation of the current collector 10 and the detachment of the material into pieces. At the same time, the porous carbon layer 40 can also reduce the resistivity on the composite current collector and shorten the migration path of lithium ions, thereby improving the overall performance of the battery cell.
[0074] In one embodiment, the compaction density of the porous carbon layer 40 is 1.0 g / cm 3 ~2.0g / cm 3 Specifically, satisfying the compaction density of the porous carbon layer 40 within the above range can ensure that some gaps are retained in the porous carbon layer 40 to absorb the gas generated after the lithium-rich material 20 is discharged. When the compaction density of the porous carbon layer 40 is too small, the porous carbon layer 40 is too loose, which not only has a poor fit with the current collector 10, resulting in a decrease in conductivity, but also falls off from the current collector; when the compaction density of the porous carbon layer 40 is too large, there are too few gaps in the porous carbon layer 40, making it difficult to absorb gas. Optionally, the compaction density of the porous carbon layer 40 can be 1.0 g / cm 3 , 1.1g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3 , 1.8g / cm 3 , 1.9g / cm 3 , 2.0g / cm 3 .
[0075] In one embodiment, the thickness of the joint portion 41 is 8 μm to 10 μm, and the thickness of the recessed portion 42 is 2 μm to 8 μm. Optionally, the thickness of the joint portion 41 may be 8 μm, 8.2 μm, 8.4 μm, 8.6 μm, 8.8 μm, 9 μm, 9.2 μm, 9.4 μm, 9.6 μm, 9.8 μm, 10 μm; the thickness of the recessed portion 42 may be 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm.
[0076] This application provides a method for preparing a composite current collector, please refer to Figure 3 and Figure 4 .
[0077] In one embodiment, the preparation method of the composite current collector is as follows: Figure 3 , specifically including the following steps:
[0078] Step S10, making grooves on the current collector.
[0079] Step S20, depositing a catalytic material and a lithium-rich material on the current collector respectively, the catalytic material is filled in the groove, and the lithium-rich material and the catalytic material are in contact with each other, so as to obtain a composite current collector.
[0080] In one embodiment, in step S10, a groove is made on the current collector, specifically comprising: placing an aluminum foil in an etching solution for electrochemical etching, and etching the groove on the current collector by controlling the power-on parameters.
[0081] In one embodiment, in step S10, the etching solution includes a mixed solution of nitric acid and hydrofluoric acid. After the aluminum foil is placed in the etching solution, a potentiostat / galvanostat and a three-electrode system are used, with a platinum mesh as a counter electrode, Ag / AgCl as a reference electrode, and a current collector as a working electrode, to electrochemically etch the current collector.
[0082] In one embodiment, in step S10, the cross-sectional shape of the grooved current collector in the thickness direction is a triangular pyramid, so during the electrochemical etching process, a voltage of 0.5 V is applied to the three-electric system for 30 seconds to produce a current collector with grooves.
[0083] In one implementation, please refer to Figure 4 In step S20, a catalytic material and a lithium-rich material are deposited in the groove respectively, including the following steps:
[0084] Step S21, depositing a catalytic material in the groove.
[0085] Step S22, depositing a lithium-rich material on the catalytic material in the groove.
[0086] In one embodiment, in step S21, catalytic material is deposited in the groove, specifically comprising: placing a current collector with a groove in a precursor solution of the catalytic material for ultrasonic immersion, and converting the precursor of the catalytic material into the catalytic material by electrochemical deposition, and depositing it in the groove.
[0087] In one embodiment, in step S21, the catalytic material is an alloy formed by a metal element and a current collector. The step of preparing a precursor solution of the catalytic material specifically includes: mixing and stirring a transition metal compound and an organic complex to form a mixed solution.
[0088] In one embodiment, in step S21, the current collector with grooves is placed in a precursor solution of the catalytic material for ultrasonic treatment and immersion, specifically including: placing the current collector with grooves in a precursor solution of the catalytic material, adding an inorganic complex to the solution to allow the inorganic complex, transition metal compound, and organic complex to react, and placing it in an ultrasonic environment for 4h-6h of ultrasonic treatment.
[0089] In one embodiment, in step S21, the precursor of the catalytic material is converted into the catalytic material by electrochemical deposition, specifically comprising: adding a brightener to a solution soaked with a current collector, using a zinc sheet as an anode, and using 1A / dm 2 -3A / dm 2 The current density is 0.2h~1h and the current collector composited with catalytic material is obtained by electroplating for 0.2h~1h.
[0090] It needs to be explained that the present application uses electrochemical deposition technology to deposit a small amount of catalytic material on the surface of the current collector by adjusting the current value, and then adds a brightener to remove the small amount of catalytic material on the coating surface, retaining the catalytic material inside the groove to achieve the above structure.
[0091] In one embodiment, in step S22, a lithium-rich material is deposited on the catalytic material in the groove, specifically comprising: mixing a current collector composited with the catalytic material with a lithium source, performing a first-stage sintering on the current collector mixed with the lithium source, and after the first-stage sintering, performing a second-stage sintering on the current collector to obtain a composite current collector after cooling.
[0092] In one embodiment, in step S22, the current collector mixed with the lithium source is subjected to a first stage of sintering, specifically comprising: placing the current collector mixed with the lithium source in a tubular furnace, and after ventilating the protective atmosphere for three hours, heating the temperature to 400°C to 500°C at a heating rate of 2°C / min, and keeping the temperature for 3h to 6h, thereby completing the first stage of sintering.
[0093] In one embodiment, in step S22, the current collector is subjected to a second stage of sintering, specifically comprising: after the first stage of sintering, continuing to heat up to 900°C to 1100°C at a heating rate of 2°C / min, and keeping the temperature for 6h to 12h, thereby completing the second stage of sintering.
[0094] It should be explained that the generation of lithium-rich materials in the present application is a method of in-situ decomposition. The precursor of the lithium-rich material will become a molten state at a certain temperature. The liquid state has fluidity and is preferentially distributed in the groove. Then the temperature is further increased to decompose it to produce lithium-rich material.
[0095] In one embodiment, the method for preparing the composite current collector further comprises, after step S20:
[0096] Step S30, forming a porous carbon layer on the surface of the current collector and the lithium-rich material.
[0097] In one embodiment, in step S30, a porous carbon layer is prepared on the surface of the current collector and the lithium-rich material, specifically comprising: spraying a conductive slurry onto the coating surface of the current collector composited with the catalytic material and the lithium-rich material, and drying after spraying to obtain a composite current collector having a porous carbon layer.
[0098] In one embodiment, in step S30, the conductive paste includes carbon material. The steps of making the conductive paste specifically include: adding the carbon material to an organic solvent to make a mixed solution, and obtaining the conductive paste after frosting, wherein the organic solvent includes a mixed solvent of tert-butyl alcohol and N-methylpyrrolidone.
[0099] In one embodiment, in step S30, the conductive slurry is sprayed onto the coating surface, specifically including: storing the conductive slurry in a container, connecting the container to a nozzle and an air compressor, adjusting the distance between the nozzle and the current collector to 15 cm to 45 cm, and continuously pumping out the conductive slurry at a speed of 5 mL / h to 50 mL / h. The conductive slurry will be dispersed into micron droplets under the action of the high-pressure annular airflow and sputtered onto the coating surface.
[0100] In one embodiment, in step S30, the drying temperature after spraying is 80° C. to 100° C. The spraying process may be repeated multiple times, and the temperature for drying again may be 100° C. to 120° C.
[0101] The present application provides a positive electrode plate.
[0102] In one embodiment, the positive electrode sheet includes a composite current collector and a positive electrode material layer 50, and the positive electrode material layer 50 is coated on the surface of the composite current collector on the side with the groove 11, and specifically, the positive electrode material layer 50 is coated on the surface of the porous carbon layer 40 away from the groove 11. The positive electrode active layer includes components such as positive electrode active material, lithium supplement material, conductive agent, binder, etc., and the present application does not specifically limit these materials, and appropriate materials can be selected according to actual application requirements.
[0103] In one embodiment, the positive electrode active material can be a phosphate positive electrode active material or a ternary positive electrode active material. In a specific embodiment, the positive electrode active material includes one or more of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium vanadium phosphate, lithium vanadium oxyphosphate, lithium fluorovanadium phosphate, lithium titanate, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide.
[0104] In one embodiment, the conductive agent includes one or more of graphite, carbon black, acetylene black, graphene, carbon fiber, C60 and carbon nanotubes, and the content of the conductive agent in the positive electrode material layer 50 is 3wt% to 5wt%.
[0105] In one embodiment, the type of binder includes one or more of polyvinylidene chloride, soluble polytetrafluoroethylene, styrene-butadiene rubber, hydroxypropyl methylcellulose, methyl cellulose, carboxymethyl cellulose, polyvinyl alcohol, acrylonitrile copolymer, sodium alginate, chitosan and chitosan derivatives, and the content of the binder in the positive electrode material layer 50 is 2wt% to 4wt%.
[0106] In one embodiment, the mass ratio of the lithium-rich material to the positive electrode active material is (1-2):50. This ratio can just make up for the loss of active lithium in the battery during the first charging process. If the proportion of lithium-rich material is too low, the active lithium lost in the positive electrode active material cannot be fully replenished, which is not conducive to improving the energy density and capacity retention rate of the battery. If the proportion of lithium-rich material is too high, the original reversible capacity will be occupied and the cost will be increased. Optionally, the mass ratio of lithium-rich material to positive electrode active material can be 1:50, 1.1:50, 1.2:50, 1.3:50, 1.4:50, 1.5:50, 1.6:50, 1.7:50, 1.8:50, 1.9:50, 2:50.
[0107] The present application provides a secondary battery.
[0108] In one embodiment, a secondary battery includes a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode includes the above-mentioned positive electrode material; the electrolyte can be an electrolyte solution, in which case the secondary battery also includes a diaphragm disposed between the positive electrode plate and the negative electrode plate; or, the electrolyte can be a solid electrolyte solution, in which case the secondary battery does not have a diaphragm and is replaced by a solid electrolyte.
[0109] In one embodiment, within the charging range of 2.5V to 4.3V, the lithium replenishment capacity of the lithium-rich material in the secondary battery is about 600mAh / g to 800mAh / g (lithium oxide); and the first coulombic efficiency is higher than the conventional one, and the capacity attenuation rate after 100 cycles is less than 3%.
[0110] The technical solution of the present application is described in detail below through specific embodiments.
[0111] Example 1
[0112] The present embodiment provides a composite current collector. The composite current collector includes a current collector (aluminum foil), a lithium-rich material (lithium oxide), a catalytic material (cobalt-aluminum alloy) and a porous carbon layer (C). A groove is formed on the current collector, and the cross-sectional shape of the groove is a triangular pyramid; the lithium-rich material and the catalytic material are both contained in the groove, and the lithium-rich material is above the catalytic material. The porous carbon layer is formed on the current collector and the lithium-rich material, and the porous carbon layer has a joint portion and a recessed portion.
[0113] The porosity of the current collector is 70%, the depth of the groove is 2 / 3 of the thickness of the current collector, and the opening diameter of the groove is 600nm. The thickness of the catalytic material is 6μm, the thickness of the lithium-rich material is 150nm, the particle size of the lithium-rich material particles is 50nm, and the mass ratio of the lithium-rich material to the catalytic material is 1:20. The thickness of the joint is 9μm, and the thickness of the recessed part is 5μm. The compaction density of the porous carbon layer is 1.5g / cm 3 .
[0114] The preparation method of the composite current collector comprises the following steps:
[0115] 1) Commercial aluminum foil (the surface morphology of aluminum foil can be referred to Figure 5 ) was placed in a mixed solution of nitric acid and hydrofluoric acid for electrochemical etching, using a potentiostat / galvanostat and a three-electrode system, in which a platinum mesh was used as a counter electrode, Ag / AgCl was used as a reference electrode, and aluminum foil was used as a working electrode. During the electrochemical etching process, a voltage of 0.5 V was applied for 30 seconds to prepare a porous aluminum foil with a triangular pyramid shape (the surface morphology of the aluminum foil can be referred to Figure 6 ).
[0116] 2) Weigh a small amount of potassium tartrate, sodium citrate, tetraethylenepentamine, and cobalt sulfate hexahydrate solids, mix them, add them to the deionized water solution and stir until a gray turbid solution is obtained. Add sodium hydroxide solution to the gray turbid solution until the solution is clear. Wrap the treated porous aluminum foil and place it in the clear solution, and ultrasonicate for 5 hours. Use zinc sheet as anode, add brightener and use 2A / dm 2 The current density was 0.5 and the current collector of the composite catalytic material was obtained by electroplating for 0.6 h.
[0117] 3) Mix the current collector of the composite catalytic material with a certain amount of anhydrous lithium hydroxide, place the anhydrous lithium hydroxide in the middle of the sheet, then slowly roll up the current collector, and then transfer it to an atmosphere tube furnace. After the protective atmosphere is ventilated for three hours, heat it to 470°C at a heating rate of 2°C / min and keep it for 4 hours, then heat it to 1000°C at a rate of 2°C / min, keep it for 8 hours, and then cool it to room temperature to obtain the current collector of the composite lithium-rich material.
[0118] 4) Add a certain amount of KB conductive carbon black to the mixed solution of tert-butanol and N-methylpyrrolidone, and obtain a conductive slurry after sand grinding. Suck the prepared conductive slurry into a 10 ml syringe equipped with a 20G needle, fix the syringe needle in the center of the fluid exchange nozzle, turn on the air compressor, adjust the distance between the fluid nozzle and the aluminum foil to 30 cm, and use a peristaltic pump to continuously pump out the conductive slurry at a speed of 25 mL / h. At this time, the high-pressure annular airflow disperses the conductive slurry into micron droplets and sprays it onto the surface of the current collector. First, roll and stretch the sprayed current collector in an oven with rollers at 100°C for drying, and then use the same process to spray the porous carbon layer for a short time. At this time, the sprayed current collector is directly transferred to the oven and dried at 120°C to obtain a composite current collector (the surface morphology of the composite current collector can be referred to Figure 7 and Figure 8 ).
[0119] Example 2
[0120] This embodiment provides a composite current collector. The difference between this composite current collector and the composite current collector provided in Embodiment 1 is that the lithium-rich material is below the catalytic material.
[0121] The difference between the preparation method of the composite current collector and the preparation method provided in Example 1 is that step 3) is performed first and then step 2).
[0122] Example 3
[0123] This embodiment provides a composite current collector. The difference between this composite current collector and the composite current collector provided in Embodiment 1 is that the cross-sectional shape of the groove is a quadrilateral, and the groove does not extend in a constricted shape.
[0124] The difference between the preparation method of the composite current collector and the preparation method provided in Example 1 is that in step 1), the applied voltage is adjusted to 1 to 1.5 V, and other conditions remain unchanged.
[0125] Example 4
[0126] This embodiment provides a composite current collector. The composite current collector is different from the composite current collector provided in Embodiment 1 in that the porosity of the current collector is 50%.
[0127] The difference between the preparation method of the composite current collector and the preparation method provided in Example 1 is that in step 1), the etching time is adjusted from 30 seconds to 15 seconds.
[0128] Example 5
[0129] This embodiment provides a composite current collector. The difference between this composite current collector and the composite current collector provided in Embodiment 1 is that the depth of the groove is 2 / 5 of the thickness of the current collector.
[0130] The difference between the preparation method of the composite current collector and the preparation method provided in Example 1 is that in step 1), a carbon rod is used as a counter electrode, and other conditions remain unchanged.
[0131] Example 6
[0132] This embodiment provides a composite current collector. The difference between this composite current collector and the composite current collector provided in Embodiment 1 is that the groove runs through the current collector.
[0133] The difference between the preparation method of the composite current collector and the preparation method provided in Example 1 is that: Step 1) a carbon rod is used as a counter electrode, the applied voltage is adjusted to 3 V, and other conditions remain unchanged.
[0134] Example 7
[0135] This embodiment provides a composite current collector. The difference between this composite current collector and the composite current collector provided in Embodiment 1 is that the opening diameter of the groove is 200 nm.
[0136] The difference between the preparation method of the composite current collector and the preparation method provided in Example 1 is that in step 1), the etching time is extended to 60 seconds, and other conditions remain unchanged.
[0137] Example 8
[0138] This embodiment provides a composite current collector. The difference between this composite current collector and the composite current collector provided in Embodiment 1 is that the opening diameter of the groove is 1 μm.
[0139] The difference between the preparation method of the composite current collector and the preparation method provided in Example 1 is that in step 1), the etching time is extended to 90 seconds, and other conditions remain unchanged.
[0140] Example 9
[0141] This embodiment provides a composite current collector. The difference between this composite current collector and the composite current collector provided in Embodiment 1 is that the thickness of the catalytic material is 1 μm.
[0142] The difference between the preparation method of the composite current collector and the preparation method provided in Example 1 is that the electroplating time in step 2) is adjusted to 0.2 hours, and other conditions remain unchanged.
[0143] Example 10
[0144] This embodiment provides a composite current collector. The difference between this composite current collector and the composite current collector provided in Embodiment 1 is that the thickness of the catalytic material is 12 μm.
[0145] The difference between the preparation method of the composite current collector and the preparation method provided in Example 1 is that the electroplating time in step 2) is adjusted to 2 hours, and other conditions remain unchanged.
[0146] Embodiment 11
[0147] This embodiment provides a composite current collector. The difference between this composite current collector and the composite current collector provided in Embodiment 1 is that the thickness of the lithium-rich material is 50 nm.
[0148] The difference between the preparation method of the composite current collector and the preparation method provided in Example 1 is that the amount of anhydrous lithium hydroxide added in step 3) is reduced.
[0149] Example 12
[0150] This embodiment provides a composite current collector. The difference between this composite current collector and the composite current collector provided in Embodiment 1 is that the thickness of the lithium-rich material is 300 nm.
[0151] The difference between the preparation method of the composite current collector and the preparation method provided in Example 1 is that in step 3), the amount of anhydrous lithium hydroxide added is increased.
[0152] Embodiment 13
[0153] This embodiment provides a composite current collector. The difference between this composite current collector and the composite current collector provided in Embodiment 1 is that the particle size of the lithium-rich material particles is 10 nm.
[0154] The difference between the preparation method of the composite current collector and the preparation method provided in Example 1 is that in step 3), the melting temperature is kept at 470° C. for 6 hours, and other conditions remain unchanged.
[0155] Embodiment 14
[0156] This embodiment provides a composite current collector. The difference between this composite current collector and the composite current collector provided in Embodiment 1 is that the particle size of the lithium-rich material particles is 100 nm.
[0157] The difference between the preparation method of the composite current collector and the preparation method provided in Example 1 is that in step 3), the melting temperature is kept at 470° C. for 2 hours, and other conditions remain unchanged.
[0158] Embodiment 15
[0159] This embodiment provides a composite current collector. The difference between this composite current collector and the composite current collector provided in Example 1 is that the compaction density of the porous carbon layer on the surface of the aluminum foil is 1.0 g / cm 3 .
[0160] The difference between the preparation method of the composite current collector and the preparation method provided in Example 1 is that in step 3), the peristaltic pump injection speed is adjusted to 45 mL / h, and other conditions remain unchanged.
[0161] Example 16
[0162] This embodiment provides a composite current collector. The difference between this composite current collector and the composite current collector provided in Example 1 is that the compaction density of the porous carbon layer on the surface of the aluminum foil is 3.0 g / cm 3 .
[0163] The difference between the preparation method of the composite current collector and the preparation method provided in Example 1 is that in step 3), the injection speed of the peristaltic pump is adjusted to 10 mL / h, and other conditions remain unchanged.
[0164] Embodiment 17
[0165] This embodiment provides a composite current collector. The difference between this composite current collector and the composite current collector provided in Embodiment 1 is that no porous carbon layer is provided.
[0166] The difference between the preparation method of the composite current collector and the preparation method provided in Example 1 is that step 4) is not performed.
[0167] Embodiment 18
[0168] This embodiment provides a composite current collector. The difference between this composite current collector and the composite current collector provided in Embodiment 1 is that the lithium-rich material is lithium oxalate.
[0169] Embodiment 19
[0170] This embodiment provides a composite current collector. The difference between this composite current collector and the composite current collector provided in Embodiment 1 is that the catalytic material is metal nickel.
[0171] Comparative Example 1
[0172] This comparative example provides a current collector (carbon-coated aluminum foil) without adding any lithium supplement agent or catalytic material.
[0173] Comparative Example 2
[0174] This comparative example provides a composite current collector. The difference between the composite current collector and the composite current collector provided in Example 1 is that the composite current collector does not contain a catalytic material.
[0175] The difference between the preparation method of the composite current collector and the preparation method provided in Example 1 is that step 2) is not performed.
[0176] Comparative Example 3
[0177] This comparative example provides a composite current collector. The difference between the composite current collector and the composite current collector provided in Example 1 is that the lithium-rich material is Li 5 FeO 4 , and there is no catalytic material, the porous carbon layer only fills the grooves.
[0178] Comparative Example 4
[0179] This comparative example provides a composite current collector. The difference between the composite current collector and the composite current collector provided in Example 1 is that no groove is formed on the current collector, and the lithium-rich material and the catalytic material are directly disposed on the current collector.
[0180] The difference between the preparation method of the composite current collector and the preparation method provided in Example 1 is that step 1) is not performed.
[0181] The composite current collector parameters provided by Examples 1 to 19 and Comparative Examples 1 to 4 are shown in Table 1:
[0182] Table 1 Composite current collector parameters provided in Examples and Comparative Examples
[0183]
[0184] The composite current collectors provided in the above-mentioned Examples 1 to 19 and Comparative Examples 1 to 4 are respectively assembled into positive electrode sheets and lithium-ion batteries according to the following methods:
[0185] Positive electrode sheet: lithium iron phosphate, SP conductive carbon black and polyvinylidene fluoride are mixed in a mass ratio of 90:4:6 through a degassing machine and an appropriate amount of N-methylpyrrolidone is added to obtain a positive electrode slurry, and the positive electrode slurry is coated on the surface of the above-mentioned current collector through a coating machine, and vacuum dried at 120°C overnight to finally obtain a positive electrode sheet;
[0186] Negative electrode: lithium sheet;
[0187] Electrolyte: Ethylene carbonate and ethyl methyl carbonate were mixed in a volume ratio of 3:7, and LiPF was added 6 , forming an electrolyte, LiPF 6 The concentration is 1 mol / L;
[0188] Diaphragm: Polypropylene microporous separator;
[0189] Lithium-ion battery assembly: Assemble button-type lithium-ion full batteries in an inert atmosphere glove box in the order of negative electrode sheet - separator - electrolyte - positive electrode sheet.
[0190] The electrochemical performance of each lithium-ion battery assembled in the above lithium-ion battery embodiment was tested under the following test conditions:
[0191] The battery was charged at a rate of 0.1C with a cut-off voltage of 4.7V; constant voltage charging was performed at a cut-off voltage of 4.7V; after the charging process was completed, the battery was allowed to stand for 10 minutes and then discharged at a rate of 0.1C with a cut-off voltage of 2.5V; the charging platform was observed during the charging process to obtain the decomposition voltage of the composite lithium supplement material; and the first cycle efficiency = (charge specific capacity / discharge specific capacity)*100%.
[0192] Pole piece volume change test:
[0193] ① Assemble a button-type full battery in a model button battery (RSS1400, IEST) purchased from Yuanneng Technology, and charge and discharge at a rate of 0.1C under a preload of 5kg, and record the expansion curve of the button-type full battery in situ; ② Then assemble the button-type half-cell of the positive electrode sheet and the SiC negative electrode sheet in a single-electrode sheet expansion test mold, and charge and discharge at a rate of 0.1C under a preload of 5kg, and record the thickness expansion change curve of the positive or negative electrode sheet in situ to obtain the corresponding expansion change.
[0194] Gas production test:
[0195] The first cycle gas production test is to assemble the lithium-ion battery with the mold battery, and then charge it with constant current and constant voltage. The first cycle charge and discharge voltage is 2.5-4.3V, the current is 0.1C, and the cut-off current is 0.01C. The gas in the mold battery is introduced into the differential electrochemical mass spectrometer for testing.
[0196] The above lithium battery test results are shown in Table 2 below:
[0197] Table 2. Test results of embodiments and comparative examples
[0198]
[0199]
[0200] From the test results of Example 1 and Example 2 and Comparative Example 1 provided in Table 2, it can be seen that Figure 5-Figure 8 It can be seen that in Example 1, evenly distributed grooves can be prepared on the surface of a commercial current collector by electrochemical etching, and the grooves are filled with lithium-rich materials and catalytic materials, and the grooves are coated with carbon materials to seal the grooves, so that the prepared composite current collector can provide a lithium replenishing effect.
[0201] From the test results of Example 1 and Example 2 and Comparative Example 2 provided in Table 2, it can be seen that by introducing a catalytic material into the composite current collector, the lithium supplement material can be further improved (the specific charge capacity and specific discharge capacity are increased). In addition, the composite current collector provided by the present application can also solve the problem of the volume change of the pole piece and the reduction of gas adsorption, and the porous carbon layer also has the function of improving the conductivity of the pole piece and adsorbing the gas produced by lithium removal.
[0202] From the test results of Example 1 and Examples 3-8 provided in Table 2, it can be seen that the surface and structure of the aluminum foil (current collector) cannot be excessively etched and modified, otherwise it is easy to cause a decrease in the conductive performance. The shape, porosity, depth of the groove and the size of the opening diameter on the current collector are controlled within a suitable range, so that the catalytic material deposited in the groove is more likely to contact and fuse with the added lithium-rich material, thereby achieving a better lithium supplementation effect.
[0203] It can be seen from the test results of Example 1 and Examples 9-14 provided in Table 2 that the electrochemical performance of the composite current collector can be adjusted by controlling the particle size and thickness of the catalytic material and the lithium-rich material contained in the groove.
[0204] It can be seen from the test results of Example 1 and Examples 15-17 provided in Table 2 that whether a porous carbon layer is provided can adjust the compaction density of the porous carbon layer, which mainly affects the gas release generated by the delithiation of the lithium-rich material and the volume change of the electrode. The presence of the porous carbon layer can significantly reduce the overall gas production of the material and inhibit the volume change of the electrode.
[0205] From the test results of Example 1, Examples 18-19 and Comparative Example 3 provided in Table 2, it can be seen that the materials (lithium-rich materials and catalytic materials) selected for the composite current collector have a certain universality and can be applied to other materials to improve the discharge capacity and cycle life of the positive electrode material and solve the gas production problem.
[0206] In the description of the embodiments of the present application, it should be noted that the orientation or positional relationship of terms such as "center", "up", "down", "left", "right", "vertical", "horizontal", "inside" and "outside" are based on the orientation or positional relationship described in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application.
[0207] What is disclosed above is only a preferred embodiment of the present application, and it certainly cannot be used to limit the scope of rights of the present application. Ordinary technicians in this field can understand that all or part of the processes of implementing the above embodiment and equivalent changes made according to the claims of the present application are still within the scope covered by the present application.
Claims
1. A composite current collector, characterized in that: The composite current collector comprises a current collector having grooves, at least part of which is filled with a catalytic material, and the composite current collector further comprises a lithium-rich material in contact with the catalytic material.
2. The composite current collector according to claim 1, characterized in that: The lithium-rich material is filled in the groove, and the filling height of the lithium-rich material and the catalytic material in the groove is not lower than the opening surface of the groove on the current collector.
3. The composite current collector according to claim 2, characterized in that: Along the thickness direction of the current collector, the thickness of the catalytic material in the groove is 2 μm to 10 μm; and / or The thickness of the lithium-rich material along the thickness direction of the current collector is 100 nm to 500 nm; and / or The lithium-rich material comprises a plurality of particles, and the particle size of the particles is 20 nm to 300 nm; and / or The mass ratio of the lithium-rich material to the catalytic material is 1:(10-20).
4. The composite current collector according to claim 1, characterized in that: The catalytic material includes a metal element and / or an alloy, and the catalytic material is sputtered on the surface of the groove.
5. The composite current collector according to claim 1, characterized in that: The porosity of the current collector is 60% to 80%; and / or The depth of the groove is 1 / 2 to 4 / 5 of the thickness of the current collector; and / or The opening diameter of the groove is 400nm to 800nm; and / or Along the thickness direction of the current collector, the groove extends in a constricted shape; and / or, At least part of the openings of the grooves are formed in one or more of a circular shape, an ellipsoidal shape, and a polygonal shape.
6. A method for preparing a composite current collector, characterized in that: include: Making grooves on the current collector; A catalytic material and a lithium-rich material are respectively deposited on the current collector, the catalytic material is filled in the groove, and the lithium-rich material and the catalytic material are in contact with each other, so as to obtain the composite current collector.
7. A positive electrode sheet, characterized in that: The positive electrode plate comprises a positive electrode material layer and a composite current collector as claimed in any one of claims 1 to 6, wherein the positive electrode material layer is coated on a surface of the composite current collector on a side where the groove is provided.
8. The positive electrode sheet according to claim 7, characterized in that: The composite current collector further comprises a porous carbon layer, which covers the surface of the current collector and the lithium-rich material; the positive electrode material layer is coated on the surface of the porous carbon layer away from the groove.
9. The positive electrode sheet according to claim 8, characterized in that: The compaction density of the porous carbon layer is 1.0 g / cm 3 ~2.0g / cm 3 .
10. A secondary battery, characterized in that: The secondary battery comprises a positive electrode, a negative electrode and an electrolyte, and the positive electrode comprises the positive electrode sheet as claimed in any one of claims 7 to 9.